Kajian Hukum terhadap Prinsip Efisiensi dan Efektivitas Penyelesaian Sengketa Konsumen melalui Lembaga Alternatif Penyelesaian Sengketa Sektor Jasa Keuangan berdasarkan POJK Nomor 61/POJK.07/2020 - Ginting, Monica Br; Lubis, Anggreni Atmei (JUNCTO: Jurnal Ilmiah Hukum, 2025)
This study examines the application of the principles of efficiency and effectiveness in resolving consumer disputes through the Alternative Institution for Financial Services Sector Dispute Resolution (LAPS SJK) based on Financial Services Authority Regulation Number 61/POJK.07/2020. Inequality in the position between financial service business actors and consumers often places consumers in a disadvantaged position. Therefore, the existence of regulations governing dispute resolution through LAPS SJK is expected to serve as a solution in providing legal protection for consumers. This research employs a normative legal approach using literature review and interview techniques for data collection. The results indicate that the dispute resolution procedure at LAPS SJK includes the submission of an application, administrative examination, mediation, and a final and binding decision. The principle of efficiency is reflected in simplified procedures and affordable costs, while the principle of effectiveness is demonstrated by fair and enforceable decisions. Although LAPS SJK has made efforts to implement these principles, several challenges remain in practice. Consequently, increased consumer education and the strengthening of LAPS SJK’s institutional capacity are necessary to enhance legal protection for financial service consumers.